Performance Validity Testing in Multiple Sclerosis. (28th November 2020) - Galioto, Rachel; Dhima, Kaltra; Berenholz, Ophira; Busch, Robyn
Abstract: Objective: Performance validity tests (PVTs) are designed to detect nonvalid responding on neuropsychological testing, but their associations with disease-specific and other factors are not well understood in multiple sclerosis (MS). We examined PVT performance among MS patients and associations with clinical characteristics, cognition, mood, and disability status. Method: Retrospective data analysis was conducted on a sample of patients with definite MS ( n = 102) who were seen for a clinical neuropsychological evaluation. Comparison samples included patients with intractable epilepsy seen for presurgical workup ( n = 102) and patients with nonacute mild traumatic brain injury (mTBI; n = 50). Patients completed the Victoria Symptom Validity Test (VSVT) and validity cutoffs were defined as <16/24 and <18/24 on the hard items. Results: In this MS cohort, 14.4% of patients scored <16 on the VSVT hard items and 21.2% scored <18. VSVT hard item scores were associated with disability status and depression, but not with neuropsychological scores, T2 lesion burden, atrophy, disease duration, or MS subtype. Patients applying for disability benefits were 6.75 times more likely to score <18 relative to those who were not seeking disability. Rates of nonvalid scores were similar to the mTBI group and greater than the epilepsy group. Conclusions: This study demonstrates that nonvalid VSVT scores are relatively common among MS patients seen for clinical neuropsychological evaluation. VSVT performance in this group relates primarily to disability status and psychological symptoms and does not reflect factors specific to MS (i.e., cognitive impairment, disease severity). Recommendations for future clinical and research practices are provided.